INTEGRATION OF PROJECT MANAGEMENT AND MANAGEMENT: NEW TRENDS IN POST-WAR NONPROFIT ORGANIZATIONS (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The aim of the article is to identify new trends in project management within nonprofit organizations. The spheres of project management and emerging trends in this field within civil society organizations have been identified. It has been established that considering the current limitation of budgetary resources directed towards meeting the needs of the security and defense sector, social protection, support for the population, and gradual economic recovery, the budget structure of Ukrainian nonprofit organizations should witness an increase in support from international donors through the implementation of social projects by them. It has been proven that civil society organizations should integrate project management with organizational management at the organizational level. The purpose of project management is not only to fulfill projects within specified timelines, without exceeding the budget, and ensuring the expected level of quality but also to create value. Therefore, projects are consolidated into portfolios. In nonprofit organizations, the project context often requires establishing a connection between projects, mission, and implementing mechanisms for integrating projects towards the adopted goals and providing resources for their implementation. Analyzing project maturity in nonprofit organizations is accomplished through the creation of a maturity map, illustrating the maturity levels of individual processes and allowing the identification of gaps in the researched areas. The use of project maturity maps allows for the improvement of project management systems and, in the long term, contributes to increasing the efficiency of implemented projects and better utilization of available resources. It is argued that projects contribute to the sustainable development of organizations. Sustainable management entails planning, monitoring, and controlling the processes of project implementation and support, taking into account the environmental, social, and economic aspects of the project lifecycle, processes, results, and consequences aimed at achieving advantages, which are carried out transparently, honestly, and ethically, involving stakeholders. This involves adopting the concept of holistic project realization, considering, in addition to classical parameters (time, cost, scope), new ones: benefits, values, risks, long-term effects for stakeholders.
Keywords: project management spheres, project maturity map, project portfolio, sustainable project management for NGOs, stakeholders, holistic project realization.